Model Komunikasi Linear - Efendi, Erwan; Attaya, Muhammad Fairuz; Nugroho, Muhammad Dimas (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
Communication is a dynamic process and involves many elements and factors. A communication is said to be effective if the message conveyed is received by the recipient of the message and obtains the same meaning. In group communication, building effective relationships is not all about personal communication because the more members there are in group communication, the more distortion it will cause. The transactional communication model is a communication model that occurs continuously and exists continuously both in sending and receiving messages, this study uses library research methods sourced from books or other reading materials. Keywords: Model, Communication, Linear Communication